Зарубинецький могильник у с. Григорівка на Дніпрі - Максимов, Є.В.; Циндровська, Л.О. (Археологія, 1995)
Публікуються матеріали з могильника зарубинецької культури в с. Григорівка Канівського району Черкаської обл. Пам’ятка значною мірою зруйнована в результаті розмиву берегів Канівським водосховищем. Аналізуються матеріали з розкопок та зібрані в прибережній зоні. В статье публикуются материалы могильника зарубинецкой культуры в с. Григоровка Каневского р-на Черкасской обл. Территория памятника в значительной степени разрушена в результате размыва берега Каневским водохранилищем. Анализируется материал из трех раскопанных погребений, а также собранный в районе смыва и происходящий, несомненно, из разрушенных захоронений. Собранный материал представлен чернолощеной и кухонной керамикой типичной для зарубинецких памятников Среднего Поднепровья. Здесь же были найдены три бронзовые фибулы, позволяющие датировать могильник, в целом, серединой ІІ в. до н. э.— І в. н. э. Findings from the sepulchre of the Zarubinets culture in vil. Grigorovka (the Kanev District, Cherkassy Region) are described in the paper. The territory of this site has significantly suffered from erosion of the Dnieper banks by the Kanev Reservoir. Findings from three excavated graves and findings collected in the area subjected to erosion and originated undoubtedly from destroyed burials are analyzed. The findings consist mainly of black- polished and kitchen pottery typical of the Zarubinets relics of the mid-Dnieper banks. At that very place three bronze-made fibules were found which permitted dating the sepulchre on the whole the mid-2nd cent. В. C. and 1st cent. A. D.